2014
DOI: 10.1071/rj14008
|View full text |Cite
|
Sign up to set email alerts
|

The sustainable development of grassland-livestock systems on the Tibetan plateau: problems, strategies and prospects

Abstract: Abstract. The Tibetan plateau is the source of most of the major rivers of Asia and has a huge impact on the livelihoods of the population, who have for centuries engaged in traditional herding practices. Sustainable management of the plateau is of critical importance not only for maintaining livelihoods but also because of its vital ecological function. The major problem of sustainable development in these grassland-livestock systems is the conflict between forage and livestock production. Despite considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(80 citation statements)
references
References 69 publications
0
79
0
1
Order By: Relevance
“…Our results suggest that a future wetter climate will be beneficial to rangeland quality, while a future dryer climate could induce forage deficiency. Without efficient adaptation strategies, overgrazing may be more frequent and severe in dryer regions, resulting in accelerated rangeland degradation (Li et al., ; Shang et al., ). Therefore, local governments should pay more attention to balance the stocking rate and forage production in reduced‐precipitation regions on the Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that a future wetter climate will be beneficial to rangeland quality, while a future dryer climate could induce forage deficiency. Without efficient adaptation strategies, overgrazing may be more frequent and severe in dryer regions, resulting in accelerated rangeland degradation (Li et al., ; Shang et al., ). Therefore, local governments should pay more attention to balance the stocking rate and forage production in reduced‐precipitation regions on the Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 99%
“…The Chinese government cites overgrazing as a major cause of grassland degradation on the Qinghai‐Tibet Plateau (Harris , Shang et al. ); however, Harris () clearly questioned those official assumptions about the causes of Tibetan grassland degradation. According to the government Forestry Bureau in 2010, overgrazing rates were estimated as follows: 38% (Tibet), 25% (Qinghai), 37% (Sichuan), and 36% (Gansu; Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, nutrition levels for livestock have declined, resulting in reduced quantities of high-quality milk being produced per animal. For example, on the Tibetan steppe region of Tianzhu (Gansu Province), a woman milks an average of four yaks daily and each yak produces only 1.5-2 kg of milk per day, which is considerably less than what was produced twenty years ago (Long et al 2008, Shang et al 2014. Zhu et al (2015) concluded that 'reducing stocking rates on heavily grazed grasslands of Northern China to moderate grazing levels would enhance NEE, and benefit biomass and animal production'.…”
Section: Carbon Management By Women Through Animal Products In Alpinementioning
confidence: 97%